2015
DOI: 10.2174/1874155x01509010527
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis and Simulation of High Pressure Water Jet Cleaning Process

Abstract: Continuous high pressure water jets currently have many industrial applications, for example, mining coal, cutting materials, and cleaning fouling layers. To gain a thorough understanding of the helix nozzle structure, which is optimized by adding an internal spiral line from a cylindrical contracting nozzle, and thereby study jetting characteristics and cleaning effectiveness, a numerical simulation method is presented to capture the features of velocity magnitude and directions and the dynamic pressure in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…近年来制造业的不断发展, 材料 成形前要对待修复及制造的关键部件进行清洗, 清洗 掉表面的污染物, 避免对制造出成形部件的应用产生 不利的影响. 传统的清洗方法包括喷砂喷丸清洗 [6] 、 化学清洗 [7] 、超声波清洗 [8] 、高压水射流清洗 [9] . 这些 人 [10] 数值模拟了准分子激光清洗膜与颗粒的温度场, 并通过实验进行验证激光清洗过程中的机制, 经分析 模拟结果与清洗实验结果一致.…”
Section: 引言unclassified
“…近年来制造业的不断发展, 材料 成形前要对待修复及制造的关键部件进行清洗, 清洗 掉表面的污染物, 避免对制造出成形部件的应用产生 不利的影响. 传统的清洗方法包括喷砂喷丸清洗 [6] 、 化学清洗 [7] 、超声波清洗 [8] 、高压水射流清洗 [9] . 这些 人 [10] 数值模拟了准分子激光清洗膜与颗粒的温度场, 并通过实验进行验证激光清洗过程中的机制, 经分析 模拟结果与清洗实验结果一致.…”
Section: 引言unclassified
“…Several studies on high-pressure cleaning have been conducted to enhance the cleaning performance through spray optimization. Zhang reported that the shape characteristics of the nozzle can enhance the performance of high-pressure cleaning [ 19 ]. Peng analytically investigated the effect of the spray distance of the nozzle on the cleaning performance [ 20 ], and Yang studied the effect of the installation of nozzle angle on the spray pressure in the spray system [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cleaning process is traditionally carried out manually. However, companies have been working towards the automation of the cleaning process [154], for example, the use of industrial high-pressure waterjet on a robotic arm for cleaning [155], or an oscillatory moving tool mounted on a robot arm [156]. Based on these literatures, before the automated cleaning process itself, it is necessary for the system to acquire data of the damaged part geometry and unclean coverage, and can be in the form of a 3D scan, or photographs.…”
Section: Cleaningmentioning
confidence: 99%